Large-scale slope instability at the southern margin of the Ediacaran Yangtze platform (Hunan province, central China) - Vernhet, E.; Heubeck, C.; Zhu, M. -Y.; Zhang, J. -M. (Precambrian Research, 2006)
Thirteen stratigraphical sections from the Doushantuo Formation, Hunan province, central China, indicate large-scale mass wasting of the Yangtze platform margin between the late Neoproterozoic glaciation and the earliest Cambrian. Numerous sedimentary discontinuities, due to regional slides, olistostromes, and stumps have modified the stratigraphy between the shallow-water carbonate platform margin and the siliciclastic slope. Slide blocks are predominantly gently deformed and are largely composed of shallow water dolomitized limestones. Slide sheets may reach a regional extent of up to similar to 5000 km(2) and are embedded in anoxic shales at an unknown water depth. (c) 2006 Elsevier B.V. All rights reserved.